PENGOLAHAN SAMPAH ANORGANIK UNTUK MENINGKATKAN PENDAPATAN MASYARAKAT DI NAGARI PAUH KAMBAR KECAMATAN NAN SABARIS - Fira, Sri Janua; Ernawati, Ernawati (JURNAL BUANA, 2025)
Abstract Processing waste can have economic value if it is done through a recycling process or recycle it into other useful objects. This research aims to describe how 1) people's income is before and after carrying out inorganic waste processing activities, 2) why inorganic waste processing is carried out, 3) what are the obstacles in the community processing inorganic waste. The research method used is descriptive with quantitative methods, population The research was the community in Nagari Pauh Kamba, Nan Sabaris District with a sample of 65 people selected using the Purpotional Random Sampling technique. Data collection uses a questionnaire. According to data obtained in the community in Nagari Pauh Kamba, the initial capital obtained was IDR. 3,480,000 and proceeds from craft sales amounting to Rp. 9,476,000. These results show that from the research data that has been processed, the value of the difference in income before and after can be seen with a significant t test value of 0.000 < 0.05, meaning the T test coefficient is accepted.Keywords— Inorganic Waste, Revenue, Proces